Effect of Heat Treatment on the Property, Structure, and Aggregation of Skim Milk Proteins - Li, Hongbo; Zhao, Tingting; Li, Hongjuan; Yu, Jinghua (Frontiers in Nutrition, 2021)
To study the mechanism of heat-induced protein aggregates, skim milk was heated at 55, 65, 75, 85 and 95 °C for 30 s. And then, the sulfhydryl content, surface hydrophobicity and secondary structure of heat-treated skim milk were studied. Treating skim milk at different temperatures induced a decrease in sulfhydryl content (75.9% at 95 °C) and an increase in surface hydrophobicity (44% at 95 °C) with a disrupted second structure containing random coil, β-sheet and β-turn of skim milk proteins. The change of these properties facilitated the aggregate formation through disulfide bonds and hydrophobicity interaction. Microstructural observation also showed a higher degree of aggregation when skim milk was heated at 85 and 95 °C. The result of two-dimensional polyacrylamide gel electrophoresis demonstrated that aggregates were consisted of a high proportion of κ-casein, β-lactoglobulin and other whey proteins.